Ivan Konevskoi : "Wise Child" of Russian Symbolism - Grossman, Joan Delaney (Studies in Russian and Slavic Literatures, Cultures, and History, 2017)
Ivan Konevskoi: "Wise Child" of Russian Symbolism is the first study in any language of Ivan Konevskoi -- poet, thinker, mystic- - for many decades the "lost genius" of Russian modernism. A fresh and compelling figure, Konevskoi plunged deeply into the currents of modern mystical thought and art in the 1890s. A passionate searcher for immortality, he developed his own version of pantheism meant to guard his unique persona from dissolution in the All-One. The poetry of Tiutchev, Vladimir Solov'ev Soloviev and Rossetti, William James's psychology, paintings of Pre-Raphaelites and Arnold Boecklin, Old Russian historical myth, the Finnish Kalevala: all engaged him during his brief life. His worldview grew more audacious, his confidence in the magical power of the word grew more assured. Drowning in 1901 at 23, Konevskoi left a legacy unfinished, rich, and intriguing.